Permainan Roda Pelangi sebagai Media untuk Meningkatkan Karakter Fairness Siswa Sekolah Dasar - Setyaputri, Nora Yuniar; Krisphianti, Yuanita Dwi; Puspitarini, Ikke Yuliani Dhian (Jurnal Kajian Bimbingan dan Konseling, 2018)
The purpose of this study was to determine the effectiveness of Roda Pelangi game to improve elementary school students’ fairness character. The research method was an experiment with a nonequivalent control group design type. The research instruments were: interview guidelines; observation guidelines; and Fairness Character Measurement Scale. The sample were twelve fourth grade students of Permata Ummat Trenggalek Integrated Islamic Elementary School that was chosen through purposive sampling. The significance score obtained based on data analysis using independent sample t-test was 0.047<0.05. The result showed Roda Pelangi game can improve elementary school students’ fairness character. Based on these results, it recommended: school counselor can use Roda Pelangi game in the guidance and counseling service process, especially to improve elementary school students’ fairness character; further researchers can use Roda Pelangi game to examine other variables and at other school levels using other research designs such as true experiment or guidance and counseling action research.